Penataan Ruang Untuk Rumah Sehat Di Desa Wisata Punthuk Ngepoh - Sekarjati, Kartinasari Ayuhikmatin; Khasanah, Rahayu; Mawadati, Argaditia (LPPM IST AKPRIND Yogyakarta, 2023)
Punthuk Ngepoh Tourism Village is a tourist village located in Banjararum Village. The pioneer in the formation of this Tourism Village was the Arum Jaya Tourism Awareness Group (POKDARWIS). Based on data from the Ministry of Environment of the Republic of Indonesia, there is the most amount of waste in household waste, namely 65.15%. So, there is a need for socialization activities for the Punthuk Ngepoh Tourism Village community. The method used in this activity is the delivery of material, understanding and knowledge by calculating the level of community understanding before and after the material is carried out, by distributing questionnaires. The target of this activity is the community of Punthuk Ngepoh Tourism Village, Banjararum Village, Kalibawang District, Kulon Progo Regency. The results obtained through this activity are that there is an increase in community understanding by 47% in the scope of knowledge about healthy homes, by 33% in the scope of knowledge about the conditions for healthy homes, by 20% in the scope of knowledge about the benefits of healthy homes, and by 67% in knowledge about the application of healthy homes